Analysis of the Role of the Kendal Regency Manpower and Industry Service in Protecting Workers' Wage Rights in Accordance with Kendal Regency Regulation Number 101 of 2021: A Qualitative Study - Sukarno, Fajar (Arkus, 2024)
Kendal is located on a strategic route between Semarang and Surabaya, the two largest metropolitan cities in Central Java. Kendal has a large working age population and is relatively cheap compared to other areas in Central Java. The district minimum wage (UMK) in Kendal is low compared to other areas in Central Java. Disnakerind has an important role in enforcing regulations and protecting workers' rights. This research aims to analyze the role of the Kendal Regency Manpower and Industry Service (Disnakerind) in protecting workers' wage rights in accordance with Kendal Regency Regulation Number 101 of 2021. This research is important to carry out because wages are a fundamental right of workers which is protected by regional laws and regulations. This research uses a qualitative method with a case study approach. Data collection techniques were carried out through in-depth interviews with key informants at the Kendal Regency Manpower and Industry Office, workers and entrepreneurs in Kendal Regency. Data were analyzed using thematic analysis techniques. The research results show that the Kendal Regency Manpower Office has an important role in protecting workers' wage rights in accordance with Kendal Regency Regulation Number 101 of 2021. This role is carried out through various activities: Socialization of regulations: Kendal Regency Manpower Office carries out socialization of regulations regarding district minimum wages (UMK) and rights. other labor rights to workers and employers; Wage inspection: Kendal Regency Manpower and Industry Office carries out wage inspections in companies to ensure that employers pay wages to workers in accordance with the UMK and other laws and regulations; Handling complaints: Kendal Regency Manpower and Industry Office receives and handles complaints from workers who feel their wage rights have been violated by employers; Worker empowerment: Kendal Regency Manpower and Industry Office provides training and assistance to workers about their rights, including wage rights. In conclusion, the Kendal Regency Manpower Office has an important role in protecting workers' wage rights in accordance with Kendal Regency Regulation Number 101 of 2021. However, there are still several challenges that the Kendal Regency Manpower Office needs to overcome so that it can carry out its role optimally.